Cover Picture: Catch‐and‐Release Probes Applied to Semi‐Intact Cells Reveal Ubiquitin‐Specific Protease Expression in Chlamydia trachomatis Infection (ChemBioChem 3/2013). Issue 3 (6th February 2013) - Claessen, Jasper H. L.; Witte, Martin D.; Yoder, Nicholas C.; Zhu, Angela Y.; Spooner, Eric; Ploegh, Hidde L.
<x xml:space="preserve">Abstract</x> The cover picture shows the delivery of a novel catch‐and‐release ubiquitin probe to cells infected with Chlamydia trachomatis. Protein ubiquitylation serves as a versatile signal involved in all areas of cell biology, and is controlled by a class of de‐ubiquitylating enzymes (DUBs). In the article on p. 343 ff, H. L. Ploegh et al. report an activity‐based probe that covalently binds to DUBs. Sortase‐mediated chemistry allowed three different cleavable linker handles to be installed on the probe, and this resulted in the efficient retrieval of bound protein. As the probe is cell impermeable, it was delivered to the cytosol of cells permeabilized with the pore‐forming toxin perfringolysin O. With this technique, the authors were able to identify great numbers of DUBs at endogenous expression level. When the technique was applied to cells infected with C. trachomatis, the authors observed expression of different host DUBs and identified two DUBs expressed by the pathogen itself. The cover was designed by Tom DiCesare (Whitehead Institute for Biomedical Research).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>